HYBRID INFORMATION MODELS IN IMAGE PROCESSING SYSTEMS - Antoshchuk, S.; Babilunga О. (International Journal of Computing, 2014)
In this article the approach to the development of hybrid information models in image processing systems is presented. This approach allowed creating more effective methods and information technologies of the image processing, analysis and recognition.